Magnetic resonance imaging of the cirrhotic liver in the era of gadoxetic acid - Agnello, Francesco (World J Gastroenterol, 2016)
Gadoxetic acid improves detection and characterization of focal liver lesions in cirrhotic patients and can estimate liver function in patients undergoing liver resection. The purpose of this article is to describe the optimal gadoxetic acid study protocol for the liver, the unique characteristics of gadoxetic acid, the differences between gadoxetic acid and extra-cellular gadolium chelates, and the differences in phases of enhancement between cirrhotic and normal liver using gadoxetic acid. We also discuss how to obtain and recognize an adequate hepatobiliary phase.